Advanced biomaterials and processing methods for liver regeneration: state‐of‐the‐art and future trends - da Silva Morais, A.; Vieira, S.; Zhao, X.; Mao, Z.; Gao, C.; Oliveira, Joaquim M.; Reis, R. L. (Advanced healthcare materials, 2020)
Liver diseases contribute markedly to the global burden of mortality and disease. The limited organ disposal for orthotopic liver transplantation results in a continuing need for alternative strategies. Over the past years, important progress has been made in the field of tissue engineering (TE). Many of the early trials to improve the development of an engineered tissue construct are based on seeding cells onto biomaterial scaffolds. Nowadays, several TE approaches have been developed and are applied to one vital organ: the liver. Essential elements must be considered in liver TEâ cells and culturing systems, bioactive agents or growth factors (GF), and biomaterials and processing methods. The potential of hepatocytes, mesenchymal stem cells, and others as cell sources is demonstrated. They need engineered biomaterialâ based scaffolds with perfect biocompatibility and bioactivity to support cell proliferation and hepatic differentiation as well as allowing extracellular matrix deposition and vascularization. Moreover, they require a microenvironment provided using conventional or advanced processing technologies in order to supply oxygen, nutrients, and GF. Herein the biomaterials and the conventional and advanced processing technologies, including cellâ sheets process, 3D bioprinting, and microfluidic systems, as well as the future trends in these major fields are discussed. The authors thank the funds obtained through the Fundo Europeu de Desenvolvimento Regional (FEDER)-funded 3BioMeD project (FCT/4773/4/5/2017/S), the Fundacao para a Ciencia e a Tecnologia (IF/00423/2012 and IF/01285/2015), and the National Key R&D Program of China (2016YFE0132700). A.d.S.M. acknowledges ERC-2012-ADG 20120216-321266 (ComplexiTE project) for his post doc fellowship. S.V. wishes to acknowledge her Fundacao para a Ciencia e a Tecnologia Ph.D. scholarship (SFRH/BD/102710/2014).